Challenges and Opportunities of the Taliban in the Process of State Building in Afghanistan: Post-American Departures - Setiawati, Siti Mutiah (Internasional Journal of Politics and Public Policy, 2025)
The withdrawal of United States troops in 2020 marked the end of the 20-year War on Terror, triggering a quick takeover of Kabul by the Taliban. This article analyzes the potential and challenges in the process of “state-building” in Afghanistan under Taliban rule, which includes the establishment of political, social, economic systems, as well as national identity. Economic dependence on foreigners and the Taliban's status as a terrorist group were the main obstacles, while people's desire to improve their living standards and support for the Islamic political system, Imarah Islam Afghanistan (IIA), were the main drivers. A qualitative approach through literature review and in-depth interviews was used for this research. Findings show that the Taliban's classification as terrorists limits global support, although the IIA offers an institutional alternative. Domestic and global obstacles are expected to test the sustainability of the Taliban regime in building a stable state.